A violência da ordem : Polícia Militar e representações sociais sobre violência em Sergipe - Souza, Marcos Santana de (2008)
The main objective of this study consists of analyzing the social representations of a group of military policemen from Sergipe about violence policeman. It was guided by a comparative perspective, the work relates the violence carried out for policemen in the State with elements of their socialization that reinforce a logic of policing destined to the control of specific social groups. In the research, 20 military policemen of the active service of MPSE (Military police from Sergipe) had been heard with the purpose of arriving to the violence policeman s social processes through the articulation among several types of representations expressed by their subjective social reality of identities, of societies and, specifically, of the violence. Besides the interviews, the research itself concentrated in the collect and examination of internal bulletins of the corporation with the purpose of identifying the orienting institutional mechanisms of the police action, what it allowed to understand as, marked by the contradictions of a moment of political opening, the state of Sergipe lived deeply the intensification of the militarists traces of the police agencies, which had passed guiding themselves for an urban version of National Safety s Doctrine (NSD), destined to the combat to the members of the popular classes, the new internal enemies. The strong presence of elements of NSD in safety s politics in the State was printed not only in the actions policemen, but also in the military policemen's representations, in general dominated by a crisis developing of identity of the internal conflicts of the institution, sensitive in the main critics of its members to the organs of defense the human rights and the democratic values, as well as in the attachment to a model of militarist formation which at the same time that marks its subjective reality it contributes for disaggregating the internal relationships.